1987
DOI: 10.1159/000309801
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Electrons Used to Inhibit Experimental Intraocular Proliferation and Detachment

Abstract: Irradiation of rabbit eyes with high-energy electrons was used to test the inhibition of experimental intraocular proliferation and retinal detachment, produced by intravitreal implantation of 250,000 homologous fibroblasts. After irradiation with 2,000 rad, started 5 days after implantation, 45% of eyes (9 of 20) still manifested traction detachment. When the dose was increased to 3,000 rad and radiation treatment was started 1 day after implantation, proliferation and traction detachment were observed in onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In doses higher than 3,000 rad (30 Gy), tissue damage could be caused by irradiation itself [20] . In another study, Binder et al [21] used a dose of 3,000 cGy (30 Gy) to inhibit proliferative vitreoretinopathy in human eyes, but did not fi nd a statistically signifi cant difference between irradiated and nonirradiated eyes.…”
Section: Discussionmentioning
confidence: 98%
“…In doses higher than 3,000 rad (30 Gy), tissue damage could be caused by irradiation itself [20] . In another study, Binder et al [21] used a dose of 3,000 cGy (30 Gy) to inhibit proliferative vitreoretinopathy in human eyes, but did not fi nd a statistically signifi cant difference between irradiated and nonirradiated eyes.…”
Section: Discussionmentioning
confidence: 98%
“…Gamma radiation has proven its antiproliferative effect in the treatment of intraocular tumors, pseudopapillar edema, and malignant exophthalmus of human eyes. Binder et al (1987) demonstrated that in the fibroblast model the fractionized radiation therapy with high energy electrons and a dose of 3000 cGy is more effective for the treatment of experimental PVR than various antiproliferative drugs (Binder 1982;Binder et al 1987;Blumenkrantz et al 1984;Lemor et al 1986;Tan0 et al 1980;Cleary & Ryan 1979). The retinal detachment rate was reduced from 85% in the control group to 10% in the treated group during a period of 6 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Reduction of this proliferation is therefore one of the main problems in this disease. Antiproliferative preparations, such as dexamethason alcohol, triamcinolone acitonide, 5-fluouracil, daunomicin, and cholchicin, have proven their effectiveness under experimental conditions (Binder 1982;Binder et al 1987;Blumenkranz et al 1984;Lemor et al 1986;Tan0 et al 1980;Cleary & Ryan 1979). Their disadvantages, however, like rapid absorption, inadequate solubility, and possible toxicity have also become manifest.…”
Section: St University Eye Clinic and University Clinic For Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experimental models of PVR have been presented (Table 1), one of them using bacteria, blood, and vital dyes long before the terms 'PVR' or 'massive periretinal proliferation (MPP)' were coined [37], and some form of trauma is always applied to the vitreoretinal interface, be it an incision [26,27], a perforating trauma [113], or the inoculation of a multitude of agents into the vitreous, mostly freshly harvested or cultured cells (Table 1). Initially, the rationale of those studies was the wish to reproduce the findings observed in human disease and to obtain a high PVR-rate for further analysis, but soon it became obvious that the real value of experimental models of PVR lies in the evaluation of surgical techniques [28,31], even more of therapeutic drugs [133], and, with minor significance, of therapeutic irradiation [12]. The latter two must be considered an adjunct to highly developed surgical techniques.…”
Section: Experimental Models Of Pvrmentioning
confidence: 99%